Analysis of Labor Productivity in Floor Plate Work Using The Work Sampling Method: Case Study: Udayana University Faculty of Medicine Building and The Calna Villa - Made Novia Indriani; I Nyoman Suta Widnyana; I Putu Agus Ari Mahendra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Labor productivity is very important in carrying out a job, in the field of construction output can be seen from the quantity of work that has been done, while input is the amount of resources used such as labor. This study aims to determine the amount of labor required per 1 m2 (OH) and the standard time for labor productivity in completing 1 m2 of floor slab work. The method of collecting primary data is the source of research data obtained directly, such as the number of workers and observation of sampling data, while secondary data is obtained from projects such as working drawings. The data is then processed using Microsoft Excel. This research is a type of quantitative research with work sampling method. From the results of research on floor slab work in the Udayana University Faculty of Medicine Building Construction project, it shows that the calculation of the volume of labor per day (OH) requires 0.011 OH masons and 0.011 OH workers and the results of calculating the standard time to complete 1 m2 of floor slab work is 3.15 minutes/m2 . The Calna Villa project shows that the calculation of the volume of labor (OH) requires 0.039 OH masons and 0.039 OH workers and the results of calculating the standard time to complete 1 m2 of floor slab work is 10.37 minutes/m2.